Using an Electrochemical MIP Sensor for Selective Determination of 1-Naphthol in Oilfield Produced Water - Bartilotti, Mariana [UNESP]; Beluomini, Maísa Azevedo [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP] (Wiley, 2021)
A molecularly imprinted polymer (MIP) sensor was successfully constructed on glassy carbon electrode for the determination of 1-naphthol (1-Nph). The sensor was constructed by electropolymerization on bare GCE in the presence of the target molecule. The recognition of 1-Nph was conducted indirectly using [Fe(CN)6]3−/4− as redox probe. The MIP sensor presented wide linear working range and limit of detection of 1.5×10−9 mol L−1. The MIP sensor was applied for the determination of 1-Nph in oilfield produced water. The results obtained showed good selectivity and sensitivity of the proposed sensor in terms of 1-Nph quantification.
Keywords: 1-Naphthol electroanalysis; electrochemical molecularly imprinted polymer; electrochemical sensor; naphthol detection; oilfield produced water